2020
DOI: 10.18632/aging.103114
|View full text |Cite
|
Sign up to set email alerts
|

Osthole alleviates neuropathic pain in mice by inhibiting the P2Y1-receptor-dependent JNK signaling pathway

Abstract: There are many reports about natural products relieving neuralgia. Osthole is the main component of Angelica biserrata Yuan et Shan, a natural product that treats rheumatism through the elimination of inflammation and the alleviation of pain that has a long history in the clinic. The analgesic mechanism of osthole is complicated and confusing. Astrocytes have attracted increasing attention from pain researchers. Inhibitors targeting astrocytes are thought to be promising treatments for neuropathic pain. Whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Reactive astrocyte-mediated neuroinflammation in the spinal dorsal horn contributes to NP [ 30 ]. Several studies have confirmed that inactivating astrocytes alleviates NP [ 31 , 32 ]. LPS has been widely applied to activate glia in vitro [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrocyte-mediated neuroinflammation in the spinal dorsal horn contributes to NP [ 30 ]. Several studies have confirmed that inactivating astrocytes alleviates NP [ 31 , 32 ]. LPS has been widely applied to activate glia in vitro [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, none of the medications are effective in neuropathic pain and have been failed in terms of effectiveness and safety [ 13 , 14 ]. In this context, natural products that present fewer side effects emerge as interesting therapeutic resources for the development of new drugs for the management of chronic pain [ 15 , 16 , 17 ]. Therefore, the development and utilization of more effective analgesic agents of natural origin that suppressed neuropathic pain remain desired.…”
Section: Introductionmentioning
confidence: 99%
“…Having determined that RIP3 and JNK were involved in pain-related behavioral changes and inflammatory responses in CCI rats, we next applied qRT-PCR and Western blotting to evaluate the expression of RIP3 and JNK in the lumbar spinal cord 1 day before and 3, 7 or 14 days after CCI. Since c-Fos expression has been reported to increase during NP [ 34 ]., we employed c-Fos as a marker of NP. On days 3, 7 and 14 after surgery, RIP3 and JNK mRNA levels in the spinal cord were greater in the CCI+NaCl group than in the control group ( P < 0.05; Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…SP600125 treatment after CCI surgery reduced JNK expression but had little effect on RIP3 expression. The expression of c-Fos (a marker of NP [ 34 ]) was also upregulated in the spinal cord after CCI, similar to RIP3; however, c-Fos was downregulated after both GSK’872 and SP600125 treatment. Immunofluorescence experiments revealed the same RIP3 expression patterns as the Western blotting and qRT-PCR assays in the lumbar spinal cord.…”
Section: Resultsmentioning
confidence: 99%